Incumbent inertia, innovativeness, and performance (dis)advantages: A demand-side learning perspective - Jonathan D. Bohlmann; Michael A. Stanko; Jelena Spanjol (AMS Review, 2024)
Abstract Strategies of incumbent firms have received considerable attention in marketing and across business disciplines, but findings regarding performance (dis)advantages and innovativeness are mixed. Prior studies on supply-side sources (factors internal to the firm) of incumbent inertia disadvantages are more prevalent than those on demand-side factors, which relate to a firm's customers and may explain potential incumbent advantages. We introduce an integrated demand-side framework to incumbent inertia, recognizing how the supply- and demand-side factors interrelate through learning mechanisms. On the one hand, incumbent firms learn and develop various routines and assets that influence their product strategies, typically reflecting inertia and incremental innovation. At the same time, customers learn about products in the market, forming preferences that reflect switching costs and network externalities (demand-side factors). Although an incumbent can gain advantages from demand-side effects, this could accelerate the onset of supply-side disadvantages. We present a set of research propositions that specify critical effects, and examine implications for incumbent strategies.
Keywords: 330; Incumbent inertia; Product innovation; Switching costs; Network externalities; Preference formation